2016
DOI: 10.1080/03601277.2016.1231511
|View full text |Cite
|
Sign up to set email alerts
|

Increased fruit and vegetable intake among older adults participating in Kentucky’s congregate meal site program

Abstract: The purpose of this study was to determine if the amount and variety of fruits and vegetables consumed increased among community-dwelling older adults participating in Kentucky's congregate meal site program following a series of five nutrition education lessons. A convenience sample of older adults attending senior centers (n=35), two intervention (n=19) and two control (n=16) centers, participated in this quasi-experimental pilot study. Following the intervention there was a significant increase in actual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Whilst other observational studies have also identified a positive association between knowledge and intake [17,27,[47][48][49][50][51][52], this study appears to be the first to provide evidence of this relationship over the long term. Previous intervention studies (typically involving a pre-post knowledge or an education component), for the most part, have found similar positive results with knowledge increasing FVI by~0.1-1.8 cups per day, within a three-month duration [53][54][55][56][57][58]. Meanwhile, a systematic review and meta-analysis by Lara et al [59] found that dietary education increased FVI by 86 g per day after 4 to 12 months, which was maintained (87 g per day) after 13-58 months.…”
Section: The Association Between Fruit and Vegetable Knowledge And Intakementioning
confidence: 77%
“…Whilst other observational studies have also identified a positive association between knowledge and intake [17,27,[47][48][49][50][51][52], this study appears to be the first to provide evidence of this relationship over the long term. Previous intervention studies (typically involving a pre-post knowledge or an education component), for the most part, have found similar positive results with knowledge increasing FVI by~0.1-1.8 cups per day, within a three-month duration [53][54][55][56][57][58]. Meanwhile, a systematic review and meta-analysis by Lara et al [59] found that dietary education increased FVI by 86 g per day after 4 to 12 months, which was maintained (87 g per day) after 13-58 months.…”
Section: The Association Between Fruit and Vegetable Knowledge And Intakementioning
confidence: 77%
“…Apart from their nutrient content, fruits and vegetables are sources of phytochemicals, such as polyphenols, that have anti-inflammatory and antioxidant actions [ 49 ]. Such protective effects could be important, as interventions to promote their consumption in older populations have been shown to be effective [ 50 , 51 ]. Unfortunately, the number of studies that examine their effects on frailty is relatively small.…”
Section: Foodsmentioning
confidence: 99%
“…Studies showed that neighborhood lunch program (NLP) participants were mostly older adults with diverse racial and income levels ( Brewer et al, 2016 ; Thomas et al, 2017 ). Older adults participating in university-based lifelong learning programs (LLP) are more likely to be white and have higher education ( Park et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%